Arterial Embolization versus Robotic Partial Nephrectomy for the Treatment of Renal Angiomyolipomas - Idir Ouzaid; Pierre-Etienne Gabriel; Byron Lee; Gauthier Delporte; Philippe Puech; Laurent Lemaitre; Evanguelos Xylinas; Arnauld Villers; Georges-Pascal Haber (International Brazilian Journal of Urology)
ABSTRACT Objective: To compare the outcomes of robotic-assisted partial nephrectomy (RALPN) and selective arterial embolization (SAE) for the treatment of sporadic renal angiomyolipoma (AML). Patients and methods: The outcomes of patients who were managed by RALPN (n = 191) or SAE (n = 51) for sporadic renal AML were matched (2:1) using a propensity score for analyses. The primary endpoint was therapeutic success defined as the absence of secondary treatment. Secondary endpoints were post-operative complications and renal function preservation (loss of eGFR at 6 months). Univariate and multivariate logistic regression analyses were used to predict factors associated with re-intervention. Results: Patients baseline characteristics in the matched population (RALP, n=96 vs. SAE, n=48) were balanced. LOS was shorter (mean: 4.2 vs. 3.1 days; p = 0.004) and EBL was lower (327 mL vs. 0 mL, p < 0.0001) in the SAE group. Overall (PN: 15.2% vs. AES: 11.7% p = 0.09) and Clavien-Dindo stratified (p = 0.62) complications were similar in both groups. After a comparable mean follow-up time (33 vs. 40 months, p = 0.63), there was an overall mean loss of eGFR of 7.7±26 mL/min/1.73m2 (p = 0.001). This loss was similar between the two groups (PN: 6.87±26 vs. AES: 11.56±23, p = 0.36). After adjusting for identified confounding factors including tumor size, type of primary intervention (RALPN vs SAE) was the only predictive factor for secondary intervention. Conclusion: RALPN was associated with decreased need for secondary treatment with no increase in morbidity compared with SAE.